2020
DOI: 10.1155/2020/4151474
|View full text |Cite
|
Sign up to set email alerts
|

Rare Presentation of Cardiotoxicity Related to 5-Fluorouracil

Abstract: 5-Fluorouracil (5-FU) is a chemotherapeutic agent frequently used for the treatment of solid tumors. In a few cases, 5-FU can be associated with coronary vasospasm, cardiac ischemia, or life-threatening arrhythmias. Recognition of 5-FU cardiotoxicity is clinically important as after the rapid sensation of therapy, cardiotoxicity can be completely reversible, and on the other hand, readministration may lead to serious damage of the heart and even death. A 70-year-old male came to the emergency department (ED) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…However, the risk of developing trastuzumab cardiotoxicity has been seen to increase in patients who receive concurrent anthracycline therapy [ 90 , 95 , 96 ]. When trastuzumab suppresses ErbB2 signaling, it was reported that it further accelerates the anthracycline’s ability to induce sarcomeric protein breakdown, increasing the chances of cardiac toxicity and heart failure [ 97 ].…”
Section: Mode Of Cardiotoxicity Inductionmentioning
confidence: 99%
“…However, the risk of developing trastuzumab cardiotoxicity has been seen to increase in patients who receive concurrent anthracycline therapy [ 90 , 95 , 96 ]. When trastuzumab suppresses ErbB2 signaling, it was reported that it further accelerates the anthracycline’s ability to induce sarcomeric protein breakdown, increasing the chances of cardiac toxicity and heart failure [ 97 ].…”
Section: Mode Of Cardiotoxicity Inductionmentioning
confidence: 99%